ANALISIS STRATEGI PENGEMBANGAN BUDIDAYA PERIKANAN BERBASIS BLUE ECONOMY - Putri Andayani,; Binar Dwiyanto Pamungkas,; Suprianto, Suprianto (Juremi: Jurnal Riset Ekonomi, 2025)
This research aims to analyze the strategy for developing blue economy-based fisheries cultivation in Sumbawa District. The research sample was 20 respondents related to aquaculture development strategies. Primary and secondary data are the types of data used in this research, where data is taken by observing and distributing questionnaires directly with respondents or the best experts and obtaining a clear understanding from existing literature. The analysis technique uses the hierarchical process analysis (AHP) method with the help of the expert choice 11 application. The results of this research show that the priority strategy for developing blue economy-based fisheries cultivation in Sumbawa district includes: 1) Establishment of a training and research center to support innovation and improvement capacity of cultivators, 2) Education for the community about the importance of BE and the impact of cultivation practices on the environment, 3) Implementation of biofloc systems, recirculating aquaculture (RAS), or aquaponics to increase efficiency, 4) Availability of access to funding, 5) Utilization of cultivation waste for added value products such as organic fertilizer, 6) Developing regulations to support the implementation of BE